Dissolution as the origin of soft-sediment deformation structures in the Upper Cretaceous of the Noumerat area (Oued Mya Basin, Algerian Sahara) - Benzina, Mostapha; Draoui, Abdelmalik; Pisarska-Jamroży, Małgorzata; Guerradi, Hocine; Hebib, Hakim; Maache, Safa (Proceedings of the Geologists' Association, 2025)
This study presents the first evidence of soft-sediment deformation structures (SSDS) within Upper Cretaceous lagoonal deposits of the Noumerat area, formed as a result of dissolution processes. Sulphates, particularly anhydrite, are well known for their susceptibility to karstification, with dissolution commonly reported as the origin of collapse breccia. However, this research introduces not only as the origin of breccia but also as a trigger for a variety of SSDS. These deformation features are primarily associated with the dissolution of anhydrite in Noumerat sedimentary succession, located on the Mzab Plateau in the Northern Algerian Sahara. As the anhydrite dissolved, the overlying claystones subsided into collapse troughs, accompanied by lateral sliding, forming distorted structures such as dome-like folds, water-escape structures, and slump structures. Furthermore, the presence of faults and cracks within the anhydrite layers significantly accelerated dissolution, promoting the formation of breccia fragments within the karst system. This underscores the chemical instability and rapid dissolution of anhydrite. The presence of secondary gypsum-bearing claystones, along with evidence of unconformity, and unconformities further supports this interpretation.